2019
DOI: 10.1126/scirobotics.aav6180
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular manipulation and measurement with multipole magnetic tweezers

Abstract: The capability to directly interrogate intracellular structures inside a single cell for measurement and manipulation is important for understanding subcellular and suborganelle activities, diagnosing diseases, and developing new therapeutic approaches. Compared with measurements of single cells, physical measurement and manipulation of subcellular structures and organelles remain underexplored. To improve intracellular physical measurement and manipulation, we have developed a multipole magnetic tweezers syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
110
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(111 citation statements)
references
References 73 publications
1
110
0
Order By: Relevance
“…Other Therapeutic Strategy : Aside from the aforementioned ferromagnetic‐particle‐based chemotherapy and hyperthermia therapy, magnetic mechanical agitation and tumor starvation therapy have been proposed in oncotherapy as well . A typical example of magnetic mechanical agitation therapy is based on magnetically responsive nanochains and nanobundles fabricated by Kralj and Makovec .…”
Section: Ferrofluid‐based Detection Diagnosis and Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Other Therapeutic Strategy : Aside from the aforementioned ferromagnetic‐particle‐based chemotherapy and hyperthermia therapy, magnetic mechanical agitation and tumor starvation therapy have been proposed in oncotherapy as well . A typical example of magnetic mechanical agitation therapy is based on magnetically responsive nanochains and nanobundles fabricated by Kralj and Makovec .…”
Section: Ferrofluid‐based Detection Diagnosis and Therapymentioning
confidence: 99%
“…As for tumor starvation therapy, magnetically responsive nanorobots which were accurately controlled by multipole magnetic tweezers have been presented currently . It was found that these magnetic nanorobots were swallowed into the living cancer cells under a magnetic field generated by magnetic coils.…”
Section: Ferrofluid‐based Detection Diagnosis and Therapymentioning
confidence: 99%
“…Magnetic manipulation of microparticles has attracted tremendous attention during the past two decades [9]- [12]. This technology is appealing because magnetic field allows non-contact manipulation and affects only magnetic particles with little impact on other objects e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This technology is appealing because magnetic field allows non-contact manipulation and affects only magnetic particles with little impact on other objects e.g. cells [9], [10]. Manipulation using magnetic fields has found a wide range of applications such as sorting and trapping of magnetically tagged micro-organisms [12], [13], sub-cellular control of signaling [14] and immunoassays [15], to name a few.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation